Družbena odgovornost kot pogoj za smiselno podjetništvo in gospodarsko rast (1) - Mulej, Matjaž (Mednarodno inovativno poslovanje, 2012)
European Union published in October 2011 a new program and new definition of social responsibility (SR) of enterprises: 'responsibility of organizations for their impacts on society'. The program essence is expressed with the sentence: by SR enterprises benefit them-selves and society. This is linked with the more globally accepted international definition in ISO 26000 that all seven central topics of SR are linked by the concepts of interdependence and holistic approach. Thus, both EU and ISO as international associations are searching for a way out from the neo-liberal practice of the economic growth at any price. The neo-liberal practice generated growth of the amount of business without growth of satisfaction of European and American population, while critically exploiting stocks of natural resources and destroying the natural environment as preconditions of human current existence; it puts practically all countries in the world in terrible debts etc. Briefly, the neo-liberal practice of economic development destroyed more than created. Such economic growth makes no sense neither makes sense the related entrepreneurship that is reduced to creation of new needs, including, or especially, fictitious needs, making the impression that it is growth of trade that makes sense rather than the growth of satisfaction of population. Sense-making investment, production, trade, and consumption (rather than self-perpetuating ones that fail to have available resources in nature as well as people's demand, hence fail to make sense) are easier to attain with more honest cooperation, listening to, hearing, and completing up of, each other that is backed better by inter-dependence (i.e. mutual need and respect for each due to mutual differences completing each other up ) other than by independence and dependence because interdependence leads to more holism. The published new sources enable creation of a new model for sense-making entrepreneurship and economic growth. The model is based on innovation of management and governance leading toward interdependence and holism that can be supported by ISO 26000 and several further references.
Keywords: corporation; družba; družbena odgovornost; ethics; etika; gospodarska rast; inoviranje; International Organization for Standardization; ISO; neoliberalizem; podjetje; podjetništvo; society; standardi; vodenje